Religion and identity politics Global trends and local realities - Matthews, Matthew; Tay, Melvin (World Scientific Publishing, 2021)
Discourse on fundamentalism has gained much attention in recent years, particularly in a post-9/11 context where extremist or terrorist threats are more prominent, perilous, and pervasive. This edited volume seeks to spotlight the perspectives of academics and practitioners vis-à-vis global trends in religious fundamentalism and right-wing extremism over the past decade. It presents a collection of works from notable academics and practitioners; including a selection of case studies from Asia to illustrate the contemporary interplay of religion, politics and identity; alongside broader global trends of religious fundamentalism.